Overnight affective dynamics and sleep characteristics as predictors of depression and its development in women. Issue 10 (20th May 2021) - Minaeva, Olga; George, Sandip V; Kuranova, Anna; Jacobs, Nele; Thiery, Evert; Derom, Catherine; Wichers, Marieke; Riese, Harriëtte; Booij, Sanne H
Abstract: Study Objectives: We examined (1) differences in overnight affective inertia (carry-over of evening affect to the next morning) for positive (PA) and negative affect (NA) between individuals with past, current, and no depression; (2) how sleep duration and quality influence overnight affective inertia in these groups, and (3) whether overnight affective inertia predicts depression development. Methods: We used data of 579 women from the East-Flanders Prospective Twin Survey. For aim 1 and 2, individuals with past ( n = 82), current ( n = 26), and without (lifetime) depression ( n = 471) at baseline were examined. For aim 3, we examined individuals who did ( n = 58) and did not ( n = 319) develop a depressive episode at 12-month follow-up. Momentary PA and NA were assessed 10 times a day for 5 days. Sleep was assessed daily with sleep diaries. Affective inertia was operationalized as the influence of evening affect on morning affect. Linear mixed-effect models were used to test the hypotheses. Results: Overnight affective inertia for NA was significantly larger in the current compared to the non-depressed group, and daytime NA inertia was larger in the past compared to the non-depressed group. Overnight NA inertia was differently associated with shorter sleep duration in both depression groups and with lower sleep quality in the current compared to the non-depressed group. Overnight affective inertia did not predict depression development at 12-month follow-up. Conclusions: Current findings demonstrate the importance of studying complex affect dynamics such as overnight affective inertia in relation to depression and sleep characteristics. Replication of these findings, preferably with longer time-series, is needed.